PREPARATION OF FUTURE SOCIAL TEACHERS TO WORK WITH MENTALLY DISABLED CHILDREN - Pavlyuk Н.В. (Pedagogy of Higher and Secondary Education, 2022)
Problems associated with the preparation of social workers to work with mentality retaeded children.